Building School Nurses' Capacity to Undertake School Dental Screening: A Pilot Project in Santa Rosa, California - Gabriel Tse Feng Chong; Andrea Pickett; Elizabeth Munns; Kristin Hoeft (Taylor & Francis Group, 2024)
ABSTRACTBackground California school nurses have cited a lack of training as an obstacle to conducting dental screenings. The objectives of this pilot project were to develop educational materials, train school nurses to perform basic dental screening examinations, and evaluate the acceptability and perceived effectiveness of the training program.Methods A two-part training program (synchronous webinar followed by practical session) to train school nurses from Santa Rosa City Schools, California, for conducting basic screening surveys was developed during the COVID-19 pandemic. This was a mixed methods study.Results At baseline, half of the nurses did not feel confident in performing dental screening (10-point Likert scale scores ranged from 2 to 4). After the training, the nurses reported enjoying the training program as well as an improvement in their knowledge and increase in confidence to 1) screen children's mouths, 2) identify decayed teeth that need treatment, 3) triage oral health care needs appropriately, and 4) refer children to a dentist (average Likert scale scores of 7-8).Conclusions The training program was acceptable to school nurses and increased their perceived capacity to perform school dental screening. This study shows that by training and educating school nurses, it is possible to build their capacity up to the point where they are empowered to confidently perform basic dental screenings.Practical Implications School-based dental programs should consider partnering with school nurses to screen for children with dental needs. This study adds to the literature on inter-sectoral collaborations and team-based partnerships to improve oral health.